2005
DOI: 10.1177/0143034305052916
|View full text |Cite
|
Sign up to set email alerts
|

Writing and Drawing Performance of School Age Children

Abstract: The aim of our study was to investigate possible relationships between writing and drawing performance of school-aged children, in order to compare the two skills at the within-individual level. The sample consisted of 182 right- and left-handed children, aged 8 to 12 years. Children were examined by the Greek adaptation of the Luria-Nebraska neuropsychological battery in spontaneous writing, copying and writing to dictation and they were asked to complete four different drawing tasks. The results produced sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 34 publications
5
20
0
Order By: Relevance
“…Finally, the results of this study also confi rm the fi ndings of recent empirical investigations (Wallen and Mackay, 1999;Bonoti et al, 2005), which indicate that there is no signifi cant difference in handwriting speed between left-and right-handed students. The surprising result that some years had twice as many left-handed students as others raises interesting questions for research around the variability of teachers' policies with regard to handedness and handwriting and around the student's perception of the issue and his or her inclination to experiment with writing with the non-preferred hand.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, the results of this study also confi rm the fi ndings of recent empirical investigations (Wallen and Mackay, 1999;Bonoti et al, 2005), which indicate that there is no signifi cant difference in handwriting speed between left-and right-handed students. The surprising result that some years had twice as many left-handed students as others raises interesting questions for research around the variability of teachers' policies with regard to handedness and handwriting and around the student's perception of the issue and his or her inclination to experiment with writing with the non-preferred hand.…”
Section: Discussionsupporting
confidence: 89%
“…Phelps et al (1985) have reported a pronounced tendency for right-handed students to write faster than left-handed students. Bonoti et al (2005) found no statistically signifi cant difference between left-and right-handed groups in drawing and writing performance, but found a greater-than-expected proportion of left-handers among poor writers. Ziviani and Elkins (1984) and Wallen and Mackay (1999) found that left-and right-handed students did not differ in handwriting speed.…”
mentioning
confidence: 69%
“…As in our study, some studies pointed out no differences between right-and left-handers in motor performances (e.g., Olex-Zarychta & Raczek, 2008;Rodrigues, Freitas, Vasconcelos, & Barreiros, 2007;Rousson, Gasser, Caflisch, & Jenni, 2009), while others had revealed that left-handed children performed worse than right-handed children (Bonoti, Vlachos, & Metallidou, 2005;Giagazoglou, Fotiadou, Angelopoulou, Tsikoulas, & Tsimaras, 2001;KastnerKoller, Deimann, & Bruckner, 2007). To support our findings, there are other two studies (Cairney et al, 2008;Goez & Zelnik, 2008) which concluded that right-handed children display higher levels of TIS in the M-ABC than lefthanded children.…”
Section: Performance In Motor Skillssupporting
confidence: 71%
“…The ability to produce a drawing is underpinned by a range of abilities, such as perception, spatial cognition and the execution of planned movements (Bonoti, Vlachos & Metallidou, 2005). As a result, drawing is a marker of both cognitive and neurobiological maturation.…”
Section: Introductionmentioning
confidence: 99%